Problems in amateur subtitling of English movies into Arabic - Khalaf, Abed Shahooth; Md Rashid, Sabariah; Jumingan, Muhammad Fauzi; Othman, Mohd Sukki (Malaysian Association of Modern Languages, 2014)
The present study sheds light on some of the problems encountered in the process of subtitling English movies into Arabic by amateur subtitling translators. It adopted a qualitative approach in the analysis of a parallel corpus, which comprised a sample of scripts of English speaking movies and their subtitles in Arabic. This sample includes the scripts of two English celebrity movies (Jarhead, 2005 and Alpha Dog, 2006) and their amateur subtitles in Arabic. The error analysis approach formulated by Bogucki (2009) was adopted with some modifications to suit the analysis approach used in this study. The English scripts and the Arabic subtitles were juxtaposed and the content analysis method was used in the codification and categorisation of the most recurrent problems in the corpus. In the translation comparison process between the source texts and their subtitled versions, Toury's (1995) 'coupled pairs' model with the back translation technique was used. The findings indicate that the most predominant problems in Arabic amateur subtitling fall within the technical, translational and linguistic domains.